Pengaruh Latihan Lompat Kardus Terhadap Hasil Lompat Jauh Gaya Jongkok Pada Siswa SD Negeri 132 Palembang - Reza Resah Pratama (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2018)
This study aims to determine how big the influence of cardboard jump exercise on the long jump style of squatting on students of State Elementary School 132 Pelembang. This type of research is experiment. Where the sample of students of State Elementary School 132 which amounted to 30 male students divided into 2 groups by ordinal pairing, ie 15 people experimental group given the treatment of cardboard jumping exercise and 15 people who were not given treatment. To determine the sample size can be calculated at least 20 - 25% of the existing popu- lation. To determine the sample by using random sampling technique and to divide the treatment and control group by ordinal pairing based on the pre test result after the research, it is concluded that there is the effect of cardboard jump exercise on the long jump style of squatting on the students of Elementary School 132 Palembang. In this cardboard jump exercise is a leaping motion that uses one leg and lands on two legs with the aim of obtaining a leap that far away. Data collection techniques used initial and final test techniques. The statistics used to analyze the data in the study using t test. The result of t test shows that ttable test = 1.70 whereas tcount = 3,49, dk = 28 and = 5%, so. Thus reject Ho and accept Ha which states there is the effect of cardboard jump exercise on the long jump style of squatting on students of Elementary School 132 Palembang.